Sim1 is a novel regulator in the differentiation of mouse dorsal raphe serotonergic neurons. - Nadja Osterberg; Michael Wiehle; Oliver Oehlke; Stefanie Heidrich; Cheng Xu; Chen-Ming Fan; Kerstin Krieglstein; Eleni Roussa (PLoS ONE)
Background Mesencephalic dopaminergic neurons (mDA) and serotonergic (5-HT) neurons are clinically important ventral neuronal populations. Degeneration of mDA is associated with Parkinson's disease; defects in the serotonergic system are related to depression, obsessive-compulsive disorder, and schizophrenia. Although these neuronal subpopulations reveal positional and developmental relationships, the developmental cascades that govern specification and differentiation of mDA or 5-HT neurons reveal missing determinants and are not yet understood. Methodology We investigated the impact of the transcription factor Sim1 in the differentiation of mDA and rostral 5-HT neurons in vivo using Sim1-/- mouse embryos and newborn pups, and in vitro by gain- and loss-of-function approaches. Principal findings We show a selective significant reduction in the number of dorsal raphe nucleus (DRN) 5-HT neurons in Sim1-/- newborn mice. In contrast, 5-HT neurons of other raphe nuclei as well as dopaminergic neurons were not affected. Analysis of the underlying molecular mechanism revealed that tryptophan hydroxylase 2 (Tph2) and the transcription factor Pet1 are regulated by Sim1. Moreover, the transcription factor Lhx8 and the modulator of 5-HT(1A)-mediated neurotransmitter release, Rgs4, exhibit significant higher expression in ventral hindbrain, compared to midbrain and are target genes of Sim1. Conclusions The results demonstrate for the first time a selective transcription factor dependence of the 5-HT cell groups, and introduce Sim1 as a regulator of DRN specification acting upstream of Pet1 and Tph2. Moreover, Sim1 may act to modulate serotonin release via regulating RGS4. Our study underscores that subpopulations of a common neurotransmitter phenotype use distinct combinations of transcription factors to control the expression of shared properties.